Economic and social factors and the quality of nutrition of pregnant women - Suliga, Edyta (Medical Studies/Studia Medyczne, 2013)
Introduction: The level of education and the social-and-economical status, connected with the amount of income, are some of the factors which decide in a significant way on the manner of a person’s nutrition. However, not much research has been carried out concerning the influence of these factors on the nutrition of pregnant women. Aim of the research: To assess the manner of nutrition of pregnant women depending on the level of education and financial resources required to buy the necessary food. Material and methods : Seven hundred and four pregnant women took part in the research. Information about social variables and the frequency of consumption of selected products and beverages, and intake of folic acid and other supplements was obtained using an anonymous questionnaire. Results: Women with the highest level of education consumed the most fruit, vegetables, milk and dairy products, saltwater fish and wholegrain foods in comparison to women with lower education; whereas they drank sweetened soft drinks less frequently. More frequent use of folic acid and other vitamin and/or mineral supplements was also connected with a higher level of education. 15.4% of pregnant women declared no sufficient financial resources to buy the necessary food. This factor was connected in a significant way to lower consumption of fruit, vegetables, products providing animal protein, milk and dairy products, saltwater fish, wholegrain products, and vitamin and/or mineral supplements. Conclusions: A lower quality of diet of pregnant women was connected both to the low level of education and the insufficient financial resources for buying the necessary food. Women with higher education, even if they had low income, chose products more consistent with the principles of proper nutrition, which confirms the positive influence of awareness and greater knowledge on their nutrition.